Clinicopathological and dermoscopic features of amelanotic and hypomelanotic melanoma: a retrospective multicentric study. (29th July 2020) - Paolino, Giovanni; Bearzi, Pietro; Pampena, Riccardo; Longo, Caterina; Frascione, Pasquale; Rizzo, Nathalie; Raucci, Margherita; Carbone, Anna; Cantisani, Carmen; Ricci, Francesco; Didona, Dario; Frattini, Francesca; et al.
Abstract: Background: Amelanotic and hypomelanotic melanoma (AHM) has a higher risk of delayed diagnosis and a significant lower 5‐year melanoma‐specific survival compared to pigmented melanoma. Our aim was the evaluation of the clinicopathological/dermoscopic features of amelanotic melanoma (AM) and hypomelanotic melanoma (HM). Methods: All participants had a personal history of AHM. We defined HM as showing clinical/dermoscopic pigmentation in < 25% of the lesion's surface and histopathological focal pigmentation, while AM as melanomas with clinical/dermoscopic and histopathological absence of pigmentation. Results: The most common phenotypic traits among the 145 AHM patients were as follows: phototype II, blue‐grey eyes, and dark brown hair. Red hair was present in 23.8% AHM cases (AM = 22.60%; HM = 25.80%). The most affected area was the back (29.5%). A total of 67.1% were classified as AM and 32.9% as HM. The most represented hair colors in AM and HM were, respectively, blonde and dark brown hair. Median Breslow thickness was 1.7 mm, superficial spreading melanoma (SSM) and nodular melanoma (NM) were the most represented histotypes, and mitotic rate > 1 × mm 2 was reported in 73.3% cases, and regression was significantly more present in HM. Dermoscopy showed high prevalence of white structureless zones (63.4%), linear looped vessels (58.8%), linear irregular vessels (50.0%), and arborizing vessels (47.2%). Multivariate logistic regression confirmed the association between the presence of pigmentation and the following: histological regression, dermoscopic globules, and arborizing vessels. Conclusions: Predominance of red hair in AHM patients was not confirmed. AHM affects mostly intermittent sun‐exposed body areas. The deeper median Breslow thickness (versus pigmented melanoma), the association of AM with the nodular histotype, and the high mitotic rate highlight the AHM's aggressiveness. HM's higher levels of regression can be explained by the presence of pigmentation, driving the underlying immune response. AHM showed a polymorphous vascular pattern and significant presence of arborizing vessels (especially HM).